The use of technologies and virtual learning environment in youth and adult Education - Marineli, Rodrigo Chechi [UNESP]; Reis, Marcia Lopes (Univ Nove Julho, 2022)
The main theme of this article was to investigate the teaching and use of Digital Information and Communication Technologies (TDIC) in Youth and Adult Education (EJA) in a public school. According to the studies carried out, the objective of this article was to define the use of TDIC and its learning possibilities with students from EJA. To this end, the research presented a literature review on education, the profile of students in the EJA modality and TDIC in the school context. The methodology was based on a qualitative approach based on field research and intervention research. The data collection technique was the use of a questionnaire with open questions. We conclude that there is a need for the inclusion of TDIC in the curriculum of EJA, focusing on digital literacy in order to guarantee students a transformative, liberating and critical.
Keywords: youth and adult education; digital information and communication technologies; teaching-learning; virtual learning environment education